Regulation of the Independent Electricity System in Batam City as a Basis for the Development of Energy Science and Technology - Rosa Darman; Huala Adolf; Riesa Susanti (Postgraduate, University of Mataram, 2025)
This study examines the regulatory framework of Batam City’s independent electricity system as a foundation for the development of energy science and technology. Batam, as a Special Economic Zone, presents a unique case of localized energy governance that integrates legal, technological, and industrial perspectives. Using a qualitative normative–juridical approach, this research analyzes national and regional energy regulations, including Law No. 30 of 2009 on Electricity and Law No. 11 of 2020 on Job Creation, to evaluate their alignment with principles of innovation and sustainability. The research findings indicate that strong regulations supported by policy incentives, research investment, academic-industry collaboration, and optimal system digitalization are essential to promote the effectiveness and independence of Batam's electricity system. This analysis identifies three interrelated stages: (1) driving factors, which include regulation strength and research funding; (2) mediating processes, covering research efficiency and technology adoption; and (3) outcomes, represented by system capacity and technological innovation. This integrative model demonstrates that adaptive, science-based regulation transforms legal frameworks into instruments for innovation, bridging the gap between policy and technological implementation. Strengthening collaboration among legal institutions, research bodies, and industrial actors is essential to advance Batam as a national model for sustainable and knowledge-driven energy governance.